Efektivitas Tanaman Sambiloto (Andrographis Paniculata) dan Senyawa Andrographolide dalam Menghambat Infeksi COVID-19 : Literature Review - Shintia Christina; Kristin Natalia Meta Kali; Reni Angeline (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Sambiloto (Andrographis paniculata) has long been used as a herbal medicine by local Indonesian people, especially because it is easy to find in the yard of the house. Since the onset of the COVID-19 pandemic, various handling efforts have been carried out, ranging from pharmacological and non-pharmacological. Various herbal plants that have the potential to be used as COVID-19 treatments have begun to be tested, including A. paniculata. To find out the benefits and mechanisms of A. paniculata in the treatment of COVID-19, a literature review study was conducted by tracing data in the form of scientific journals published in the last 2 years since the pandemic began. At the end of the results of this study, A. paniculata demonstrated its function in inhibiting COVID-19 through the mechanism of preventing virus attachment to surface receptors and inhibiting viral replication.